New Characterizations for Minimizing Energy of Biharmonic Particles in Heisenberg Spacetime - Körpınar, Talat (Springer New York LLC, 2014)
In this work, we study energy of timelike biharmonic particle in a new spacetime Heisenberg spacetime H14. We give a geometrical description of energy of a Frenet vector fields of timelike biharmonic particle in H14 Moreover, we obtain different cases for this particles. © 2014 Springer Science+Business Media New York.
Keywords: Bienergy; Biharmonic particle; Energy; Heisenberg spacetime